The Role of Rice Husk Charcoal and Cow Manure on The Availability of Nutrients and Yield of Cherry Tomatoes (Solanum lycopersicum) on Ultisol Soil - Suswati, Denah; Murni, Sri Dewi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Ultisol as a growing medium for cultivated plants requires proper management because it has chemical limiting factors, namely acidic soil pH, availability of macro and micro nutrients and low base saturation. Acidic soil reaction in Ultisol soil can cause nutrients, especially P and Ca, to be less available while Fe, Al and Mn nutrients are in excessive amounts so that they become toxic to plants. The purpose of this study was to obtain a combination of rice husk charcoal and cow manure doses that can increase the availability of macro nutrients and the highest yield of Cherry Tomato plants on Ultisol soil. The technique is a Completely Randomized Factorial Design (CRD Factorial), with 48 experimental units made up of the first treatment (a dose of rice husk charcoal with four treatment levels) and the second treatment (a dose of cow manure with four treatment levels) repeated three times. As demonstrated by the study's findings, the A3S3 treatment (rice husk charcoal 2,250 g/polybag, cow manure 3,000 g/polybag) can raise pH by 370.86%, increase nutrient availability (N, P, K, Ca, Mg, and Na) by 121.74%-539.39%, and increase crop yields (number of fruits per plant and fruit weight per plant) of corn in Ultisol soil by 230.27%-370.86% when compared to the A0S0 treatment.